New data on nomenclature, taxonomy and distribution of some species of the lichen genus "Cladonia" - Ahti, Teuvo; Stenroos, Soili (Botanica Complutensis, 2012)
The name Cladonia diversa Asperges ex S. Stenroos is validated, and the species is reported as new to Japan. Cladonia angustiloba, earlier known from Macaronesia, is reported to extend to Faeroe Is., Denmark. Cladonia aspera Ahti & Kashiw. is an illegitimate later homonym of C. aspera (Flörke) Doign. The former name is still regarded as a synonym of C. sarmentosa, while the latter name is a synonym of C. gracilis subsp. gracilis. The type of C. dilleniana is stated to be from Bahama Islands rather than Turks and Caicos Islands. The volcano lichen C. vulcani is recorded from Iceland as new to Europe. The author citation of C. bacilliformis (Nyl.) Sarnth. and type location citation of C. glauca Flörke are corrected. Se valida el nombre Cladonia diversa Asperges ex S. Stenroos y se reporta nueva para Japón. Cladonia angustiloba, anteriormente conocida de la Macaronesia extiende su área de distribución hasta las islas Feroe, Dinamarca. Cladonia aspera Ahti & Kashiw. es el último homónimo ilegitimo de C. aspera (Flörke) Doign. El primer nombre válido es considerado un sinónimo de C. sarmentosa, mientras que este último es un sinónimo de C. gracilis subsp. gracilis. El tipo de C. dilleniana procede de las islas Bahamas en lugar de las islas Turcos y Caicos. El liquen de los volcanes C. vulcani se cita de Islandia y constituye nueva cita para Europa. Se corrige la autoría de C. bacilliformis (Nyl.) Sarnth. y la indicación locotípica de C. glauca Flörke.